Concentrate and degrade PFOA with a photo-regenerable composite of In-doped TNTs@AC - Jan-Max Arana Juve; Li, Fan; Yangmo Zhu; Liu, Wen; Lars D.M. Ottosen; Zhao, Dongye; Zongsu Wei (Chemosphere, 2022)
“Concentrate-and-degrade” is an effective strategy to promote mass transfer and degradation of pollutants in photocatalytic systems, yet suitable and cost-effective photocatalysts are required to practice the new concept. In this study, we doped a post-transition metal of Indium (In) on a novel composite adsorptive photocatalyst, activated carbon-supported titanate nanotubes (TNTs@AC), to effectively degrade perfluorooctanoic acid (PFOA). In/TNTs@AC exhibited both excellent PFOA adsorption (>99% in 30 min) and photodegradation (>99% in 4 h) under optimal conditions (25 °C, pH 7, 1 atm, 1 g/L catalyst, 0.1 mg/L PFOA, 254 nm). The heterojunction structure of the composite facilitated a cooperative adsorption mode of PFOA, i.e., binding of the carboxylic head group of PFOA to the metal oxide and attachment of the hydrophobic tail to AC. The resulting side-on adsorption mode facilitates the electron (e‒) transfer from the carboxylic head to the photogenerated hole (h+), which was the major oxidant verified by scavenger tests. Furthermore, the presence of In enables direct electron transfer and facilitates the subsequent stepwise defluorination. Finally, In/TNTs@AC was amenable to repeated uses in four consecutive adsorption-photodegradation runs. The findings showed that adsorptive photocatalysts can be prepared by hybridization of carbon and photoactive semiconductors and the enabled “concentrate-and-degrade” strategy is promising for the removal and degradation of trace levels of PFOA from polluted waters.
Keywords: Adsorptive photocatalyst; Concentrate-and-degrade; Electron-hole recombination; Heterojunction; Perfluorooctanoic acid